Digital Capability, Digital Transformation, and Digital Innovation as Determinants of Food Stall Business Performance in South Tangerang City - Rayhan Aimar Nawawi; Hujjatullah Fazlurrahman; Renny Sari Dewi; Achmad Kautsar (JURNAL ECONOMINA, 2026)
This study is motivated by the rapid digitalization of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly through online ordering platforms, delivery services, social media, and digital payment systems such as QRIS. However, digital adoption does not always improve business performance, especially among food stall MSMEs that still face challenges such as declining profit margins, platform dependency, and limited internal readiness. This study aims to analyze the influence of Digital Capability, Digital Transformation, and Digital Innovation on the Business Performance of food stall MSMEs in South Tangerang City. This research used a quantitative approach with an explanatory research design. The sample consisted of food stall owners or managers who had operated for at least one year, adopted digital technology, and were directly involved in business decision-making. Data were collected through a closed-ended questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results show that Digital Capability has a positive and significant effect on Business Performance, with a path coefficient of 0.242 and a P-value of 0.042. Digital Transformation has the strongest effect, with a path coefficient of 0.356 and a P-value of 0.005. Digital Innovation also has a positive and significant effect, with a path coefficient of 0.242 and a P-value of 0.026. The R² value of 0.564 indicates that the three variables explain 56.4% of the variation in Business Performance. Therefore, this study concludes that improving MSME performance requires digital capability, business process transformation, and sustainable digital innovation.